Mineralizing Filamentous Bacteria from the Prony Bay Hydrothermal Field Give New Insights into the Functioning of Serpentinization-Based Subseafloor Ecosystems - Pisapia, Céline; Gérard, Emmanuelle; Gérard, Martine; Lecourt, Léna; Lang, Susan Q.; Pelletier, Bernard; Payri, Claude E.; Monnin, Christophe; Guentas, Linda; Postec, Anne; Quéméneur, Marianne; Erauso, Gaël; et al. (Frontiers in Microbiology, 2017)
Despite their potential importance as analogs of primitive microbial metabolisms, the knowledge of the structure and functioning of the deep ecosystems associated with serpentinizing environments is hampered by the lack of accessibility to relevant systems. These hyperalkaline environments are depleted in dissolved inorganic carbon (DIC), making the carbon sources and assimilation pathways in the associated ecosystems highly enigmatic. The Prony Bay Hydrothermal Field (PHF) is an active serpentinization site where, similar to Lost City (Mid-Atlantic Ridge), high-pH fluids rich in H2 and CH4 are discharged from carbonate chimneys at the seafloor, but in a shallower lagoonal environment. This study aimed to characterize the subsurface microbial ecology of this environment by focusing on the earliest stages of chimney construction, dominated by the discharge of hydrothermal fluids of subseafloor origin. By jointly examining the mineralogy and the microbial diversity of the conduits of juvenile edifices at the micrometric scale, we find a central role of uncultivated bacteria belonging to the Firmicutes in the ecology of the PHF. These bacteria, along with members of the phyla Acetothermia and Omnitrophica, are identified as the first chimneys inhabitants before archaeal Methanosarcinales. They are involved in the construction and early consolidation of the carbonate structures via organomineralization processes. Their predominance in the most juvenile and nascent hydrothermal chimneys, and their affiliation with environmental subsurface microorganisms, indicate that they are likely discharged with hydrothermal fluids from the subseafloor. They may thus be representative of endolithic serpentinization-based ecosystems, in an environment where DIC is limited. In contrast, heterotrophic and fermentative microorganisms may consume organic compounds from the abiotic by-products of serpentinization processes and/or from life in the deeper subsurface. We thus propose that the Firmicutes identified at PHF may have a versatile metabolism with the capability to use diverse organic compounds from biological or abiotic origin. From that perspective, this study sheds new light on the structure of deep microbial communities living at the energetic edge in serpentinites and may provide an alternative model of the earliest metabolisms.